Living: lifelong learning (Journal of Parents and Teachers, 1996)
The importance of lifelong learning and the use of stories and narratives to facilitate understanding and interest in various subjects. It highlights how personal experiences and narratives can transform education, making it more engaging and meaningful. In addition, the complexity of life and the need to adapt to it through knowledge is mentioned.
Keywords: lifelong learning; understanding; meaningful education